Memories of Discipline in Soviet Lithuania: Stories in Oral History - Ulinskaitė, Jogilė (Baltic Journal of Political Science, 2018)
Totalitarian regimes attempt to restrict and control virtually every aspect of human life. Interestingly, conscious reflection on disciplinary practises takes up only a small part of the life-stories of interviewed Lithuanians, as far as the memory of the post-Stalin era is concerned. The interviews that form the foundation for this paper were conducted during the summer of 2017 in three different districts in Lithuania. The article aims to answer the following two research questions: 1) Which mechanisms of discipline did people recognize and reflect upon? 2) How were disciplinary actions remembered and described? According to interviews, tangible individuals filled the role of disciplinarians in schools and workplaces. In addition, the responsibility for discipline and control lies within the imperceptible disciplinarian, supplemented by the invisible discipline of the collective. This led to overwhelming uncertainty in the society, where people invoked intuition and interpretations of who is trustworthy to adapt to uncertain situations. The greatest impact of the totalitarian discipline was that people effectively internalized it and consequently became their own most significant disciplinarians.